Análise da relação entre vitiligo e síndrome metabólica - Grando, Elisa (2014)
Vitiligo is an acquired, depigmenting disorder. The etiology is unknown, but mostly autoimmune, associated with high levels of pro-inflammatory cytokines. These cytokines would stimulate atherosclerosis and develop metabolic syndrome. The aim of this study was to evaluate the relationship between vitiligo and metabolic syndrome. This is a transversal study, with 96 patients (47 with and 49 without vitiligo) treated at Hospital Universitário de Santa Maria RS, from March 2013 to January 2014. The vitiligo patients were selected by clinical diagnosis and the criteria of extension and time of disease were evaluated. The diagnostic criteria for metabolic syndrome were assessed, following IDF: total cholesterol, high-density lipoprotein-cholesterol (HDL-c), triglycerides, waist circumference and blood pressure. We evaluated the insulin resistance through the homeostasis model assessment-insulin resistance (HOMA-IR). The MS prevalence between the groups does not show significant difference (36,2% vs. 38,3%, p=1,000). Waist circumference was different between groups (95,5 vs. 90,5 cm). Vitiligo group showed smaller levels of HDL-c (48,2 mg/dL vs 57,7 mg/dL, p<0,001), and this difference was sustained in the sub-analysis of female patients. HOMA-IR did not show difference between groups. Metabolic syndrome was not associated with extension and evolution time of vitiligo. This study did not reveal relation between vitiligo and MS. HDL-c was smaller in vitiligo patients, and there was inverse correlation (r = -0,30, p = 0,045) between HDL-c and insulin only in vitiligo group.